Asessment of Vehicle Maintenance Culture and Its Cost Effectiveness: Case of University for Development Studies - Seniwoliba, Joseph Attiah (European Scientific Journal, ESJ, 2022)
The study assessed the maintenance culture of vehicles and the associated costs in the University for Development Studies at the Central Administration, Tamale Campus in order to provide solutions to maintenance problems facing the University with the associated high cost of maintenance. The study considered all 55 vehicles and drivers at the Central Administration used by various offices, directorates and general use (pool). However, data on 34 vehicles were available which is far more than the needed representation. Ten drivers were sampled to participate in the study using the simple random sampling approach. Face-to-face interviews with one-on-one respondents were conducted with the selected drivers. The researcher used open ended questions to gather relevant data from the respondents. The secondary data was obtained from mechanics and technicians who had presented their bills for payment at the Transport Office. Both the qualitative and quantitative methods were used in analyzing the data collected. The Grounded Theory and excel sheets were employed for the data analysis. The study revealed that that the poor maintenance culture is as a result of poor funding, delay in the release of funds for maintenance, inflation of the cost of spare parts, design errors, use of sub-standard materials, age of vehicles, insufficient knowledge and skills of mechanics and technicians were factors identified as those contributing to problems of effective maintenance culture. It is therefore recommended that a formalized maintenance department should be established with well qualified and experienced personnel with practical knowledge and skills in vehicle maintenance and with a well-equipped workshop with the necessary tools and spare parts. This will allow fast and quick response to vehicle maintenance issues.